2019
DOI: 10.1590/1980-5373-mr-2019-0311
|View full text |Cite
|
Sign up to set email alerts
|

Molten Salt Synthesis of Bi2WO6 Powders and its Visible-Light Photocatalytic Activity

Abstract: Bi 2 WO 6 powders were synthesized by the molten salt method at 250-350 ºC using the mixture of Bi(NO 3) 3 •5H 2 O and Na 2 WO 4 •2H 2 O as a precursor, and the mixture of LiNO 3 and NaNO 3 with a molar ratio of 27:33 as a molten salt, respectively. The effects of temperature and salt amount on the phase composition, morphology and photocatalytic activity under the visible light irradiation were investigated. The results revealed that pure phase Bi 2 WO 6 powders could be synthesized at 350 ºC as the weight of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…These findings indicated that ANS catalyst exhibited better visible light absorption than NaSbO 3 after doping with Ag atom. For the calculation of band gap energy, Tauc equation is often used as follows: 55,56 where, α, h, v, A and Eg represents absorption coefficient at light frequency v, Planck constant, light frequency, a constant and band gap energy, respectively. For direct transition semiconductor as NaSbO 3 , the value of n is 1.…”
Section: Uv-vis Diffuse Reflectance Spectramentioning
confidence: 99%
“…These findings indicated that ANS catalyst exhibited better visible light absorption than NaSbO 3 after doping with Ag atom. For the calculation of band gap energy, Tauc equation is often used as follows: 55,56 where, α, h, v, A and Eg represents absorption coefficient at light frequency v, Planck constant, light frequency, a constant and band gap energy, respectively. For direct transition semiconductor as NaSbO 3 , the value of n is 1.…”
Section: Uv-vis Diffuse Reflectance Spectramentioning
confidence: 99%
“…Actually, the use of semiconductor materials reduces the costs of heterogeneous photocatalysis and enables the mineralization of various organic compounds without any additive [14]. Several semiconductors have been used in photocatalytic degradation of environmental contaminants, including titanium dioxide (TiO 2 ), zinc oxide (ZnO), tungsten oxide (WO 3 ), tin oxide (SnO 2 ), zirconium oxide (ZrO 2 ), cadmium sulfide (CdS), and others [14,[16][17][18][19][20][21][22][23]. Among many semiconductors, TiO 2 has attracted much attention by different research groups [24][25][26][27][28] because it is inexpensive and chemically stable [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…is plotted against the hν , where α is the absorption coefficient of material and represents the probability of light being absorbed per unit path length 7 . Consequently, the unit of measure for h α ν is unit of energy divided by unit of length and not eV as declared by the authors 1 . However, as the values presented on the ordinate axis in the inset shown in Figure 5 were obtained from the absorbance measurements, the most appropriated unit for h α ν is "arbitrary unit".…”
mentioning
confidence: 99%